Pengaruh Kualitas Pelayanan, Persepsi Nilai dan Citra Merek Terhadap Loyalitas Pelanggan Pengguna Jasa Gojek di Kota Denpasar - I Kadek Adi Suradana; I Gusti Ayu Imbayani; Made Pradnyan Permana Usadi (Lembaga Pengembangan Kinerja Dosen, 2026)
Customer loyalty is a critical determinant of service sustainability amid increasingly dynamic competition in the online ride-hailing industry. This study aims to examine the effects of service quality, perceived value, and brand image on customer loyalty among Gojek users in Denpasar City. The research employed an associative quantitative approach with purposive sampling of 150 respondents, namely Gojek users residing in Denpasar who used the application at least once a week. Data were collected through a Likert-scale questionnaire, interviews, and documentation. The research instrument met validity and reliability criteria, and the data were analyzed using multiple linear regression along with classical assumption tests. The results indicate that service quality has a positive and significant effect on customer loyalty (β = 0.240; p < 0.05), perceived value has a positive and significant effect on customer loyalty (β = 0.326; p < 0.05), and brand image has a positive and significant effect on customer loyalty (β = 0.413; p < 0.05). Simultaneously, these three variables explain 69.4% of the variance in customer loyalty (Adjusted R² = 0.694), and the model is considered fit (F = 113.659; p < 0.05). These findings suggest that strengthening brand image, improving service quality, and enhancing customers’ perceived value should be prioritized as key strategies for Gojek to maintain user loyalty in Denpasar City.